The Innovation of MOOC Based E-Marketing to Improve Entrepreneurship Administration Management for Vocational Education Students in Industrial Revolution 4.0 Era - Putra, Andika Bagus Nur Rahma; Mukhadis, Amat; Tuwoso, Tuwoso; Ulfatin, Nurul; Wonorahardjo, Surjani; Habiddin, Habiddin; Degeng, Made Duananda Kartika; Tee, Tze Kiong (Universitas Negeri Malang, 2020)
Abstract: This research has aims to: (1) develop MOOCs based e-marketing; (2) testing theattractiveness of MOOCs based e-marketing; and (3) knowing the level of effectiveness ofMOOCs based e-marketing. The method in this study is research and development. The resultsof this study include: (1) the results of the e-marketing expert test and website marketing designexpert test have a percentage: 81.50% (ease of accessing consumers), 84.10% (presentation ofgoods/services sold), 79.10 % variation of website content), 86.00% (compatibility with websitegoals), 83.70% (harmony of each page of views), 83.70% (complete description of products sold),83.70% (attractiveness of e-website marketing), 85.00% (ease of order process for consumers),81.50% (responsible admin e-marketing), 81.50% (trouble shooting website problems); (2)MOOCs based e-marketing proved effective in improving the management of studententrepreneurship administration in the vocational sector in the Industrial Revolution 4.0 era,indicated by the results of the final ability test which showed significant differences betweencontrol classes without using e-marketing based MOOCs and experimental classes using MOOCsbased e-marketing; and (3) E-marketing based MOOCs needs to be further developed because itcan improve the management of entrepreneurial administration in vocational students in theIndustrial Revolution era 4.0.